The Effect of Firm Size and Sales Growth on The Capital Structure and Financial Performance of The Tourism Industry in Indonesia - Widawati, Ida Ayu Putri (E-Journal of Tourism, 2023)
The purpose of this study is to examine the effect of firm size and sales growth on the capital structure on the tourism industry and the effect of firm size, sales growth, and capital structure on the financial performance of a firm in the tourism industry that is listed on the Indonesia Stock Exchange (IDX). The sampling technique used a purposive sampling method for the tourism industry companies based on the determined criteria; 21 tourism industry companies that were listed on the Indonesia Stock Exchange in the 2013–2016 period were selected as samples. This research applies a classic assumption test and the multiple regression analysis technique using statistic test on Statistical Package for Social Science (SPSS) version 20. The results of the analysis indicate that firm size has a positive influence on a firm's financial performance; meanwhile, the capital structure has a negative effect on financial performance. Sales growth was found to not have any influence on the financial performance. Similarly, firm size and sales growth did not have any effect on the capital structure.   Keywords : Firm size, sales growth, capital structure, financial performance